"I Can Math!": Reducing Math Anxiety and Increasing Math Self-Efficacy Using a Mindfulness and Growth Mindset-Based Intervention in First-Year Students. Issue 3 (4th March 2021) - Samuel, Tashana S.; Warner, Jared
ABSTRACT: Math anxiety is a debilitating problem that affects many community college students. Neuropsychological research suggests that negative rumination when anticipating math situations substantially exhausts working memory load, contributes to execution anxiety, which interferes with learning and performance. Studies have shown that improving the psychological experience in the classroom could have a positive impact on students' academic achievement. However, there is little to no research employing interventions designed to specifically address anticipation and execution math anxiety in community college students. The current research investigated the effect of embedding a combined mindfulness and growth mindset intervention within a required first-year, two-semester developmental statistics course. Results from this mixed methods pilot study indicate that this new combined approach not only reduced math anxiety, but had also increased math self-efficacy in a sample of college students. Replication of the research is warranted in order to substantiate the preliminary results.